Sustained Negative Mental Health Outcomes Among Healthcare Workers Over the First Year of the COVID-19 Pandemic: A Prospective Cohort Study - Roberto Mediavilla; Roberto Mediavilla; Roberto Mediavilla; Eduardo Fernández-Jiménez; Eduardo Fernández-Jiménez; Irene Martinez-Morata; Irene Martinez-Morata; Fabiola Jaramillo; Fabiola Jaramillo; Jorge Andreo-Jover; Jorge Andreo-Jover; Inés Morán-Sánchez; et al. (Frontiers Media S.A., 2022)
Objective: To characterize the evolution of healthcare workers' mental health status over the 1-year period following the initial COVID-19 pandemic outbreak and to examine baseline characteristics associated with resolution or persistence of mental health problems over time.Methods: We conducted an 8-month follow-up cohort study. Eligible participants were healthcare workers working in Spain. Baseline data were collected during the initial pandemic outbreak. Survey-based self-reported measures included COVID-19-related exposures, sociodemographic characteristics, and three mental health outcomes (psychological distress, depression symptoms, and posttraumatic stress disorder symptoms). We examined three longitudinal trajectories in mental health outcomes between baseline and follow-up assessments (namely asymptomatic/stable, recovering, and persistently symptomatic/worsening).Results: We recruited 1,807 participants. Between baseline and follow-up assessments, the proportion of respondents screening positive for psychological distress and probable depression decreased, respectively, from 74% to 56% and from 28% to 21%. Two-thirds remained asymptomatic/stable in terms of depression symptoms and 56% remained symptomatic or worsened over time in terms of psychological distress.Conclusion: Poor mental health outcomes among healthcare workers persisted over time. Occupational programs and mental health strategies should be put in place.